Whey as cause of high mortality in cattle Soro de leite como causa de alta mortalidade de bovinos - Gava A.* (2018)
© 2018 Colegio Brasileiro de Patologia Animal.This study reports the epidemiological data, clinical signs and lesions produced in the rumen by ingestion of fermented whey. 160 cattle have become ill, including cows, heifers and calves, 87 of them died. One day after being given 6000 liters of whey, the cattle showed loss of appetite, staggering gait, endophthalmitis, diarrhea with gray coloration and malodorous, and they lay down and raised frequently. Necropsy findings were consistent in the rumen and were characterized by congestion of vessels of serous and marked distention of the wall, allowing seeing the internal content, which was liquid, greyish and fetid. The mucosa was reddish with junction of the buds forming small masses of firm consistency. In the abomasum the mucosa was dark red, fuzzy. Histological lesions in the rumen consisted of vacuolar degeneration with formation of vesicles, multifocal necrosis accompanied by neutrophilic infiltrate, sometimes with fibrin deposition, besides thickening of the keratinized mucosa layer.